Does self-medication reduce medical expenditure among the middle-aged and elderly population? A four-wave longitudinal study in China - Zheng, Zehao; Feng, Zhanchun; Zhang, Donglan; Sun, Xiaobo; Dong, Dong; Luo, Youxi; Feng, Da (Frontiers in Public Health, 2023)
Introduction: Self-medication has a high prevalence among middle-aged and elderly population in China. Despite the published evidence demonstrating the economic benefits of self-medication, limited research has addressed the relationship between self-medication and individual medical expenditures, especially in Chinese populations. This study examines the effect of self-medication on individual medical expenditures in China, and analyzes the heterogeneity between outpatient and inpatient cases. Methods: We conducted a panel data analysis using data from four waves of China Health and Retirement Longitudinal Study (CHARLS). Two-part mixed-effect models were implemented to estimate the effect of self-medication on total outpatient and inpatient expenses and out-of-pocket (OOP) costs, where mixed-effects logit regression was used as the first-part and generalized linear mixed models with log link and gamma distribution as the second-part. Results: We identified 72041 responses representing 24641 individuals, of which 13185 responses incurred outpatient expenses and 9003 responses incurred inpatient costs. Controlling for all covariates, we found that self-medication behaviors were significantly associated with a higher probability of outpatient service utilization (OR=1.250, 95% CI= 0.179 to 0.269; P<0.001), but displayed no significant association with outpatient expenses. Respondents who had taken self-medication were less likely to use inpatient service (OR=0.865, 95% CI=-0.201 to -0.089; P<0.001), and their inpatient expenses were significantly reduced by 9.4% (P<0.001). Inpatient OOP costs were significantly reduced by 10.7% (P<0.001) and outpatient OOP costs were significantly increased by 11.3% (P<0.001) among respondents who had self-medicated. Conclusions: This study allowed us to identify the economic value of self-medication among the middle-aged and elderly population in China. Future work should guide the middle-aged and elderly to take responsible self-medication to reduce the economic burden.